2011
DOI: 10.1177/097265271101000201
|View full text |Cite
|
Sign up to set email alerts
|

CDS Pricing and Elections in Emerging Markets

Abstract: To study the role of elections in financial market instability, we focus on the role of credit risk pricing during elections from 2004 to 2007 in 13 emerging market economies. We use a unique dataset of daily credit default swap (CDS) pricing, with standard macroeconomic controls, to study the role of elections in prompting financial market instability and contagion. Sovereign CDS pricing provides a number of advantages in understanding emerging market instability of previous studies. First, the daily data all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Spread changes rely less on political variables and fundamentals, and more on market sentiment (Eichengreen and Mody 1998). Balding (2011) and Özatay et al (2009) point to the effect of herding behavior on emerging countries' sovereign bonds market and find substantial contagion effects. Yield inflation of one emerging economy influences neighbouring countries, even when neighbours do not suffer any negative changes in economic outlooks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spread changes rely less on political variables and fundamentals, and more on market sentiment (Eichengreen and Mody 1998). Balding (2011) and Özatay et al (2009) point to the effect of herding behavior on emerging countries' sovereign bonds market and find substantial contagion effects. Yield inflation of one emerging economy influences neighbouring countries, even when neighbours do not suffer any negative changes in economic outlooks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the fear of losing an important source of external funding may suppress temptations to generate electoral credit cycles. In particular, governments that rely on international bond markets for financing may face an even weaker temptation for credit market manipulation (Balding, 2011; Kaplan, 2013).…”
Section: Synthesis and Hypothesesmentioning
confidence: 99%
“…Sobel (2002) and Mosley (2003) find the threat of exit by mobile asset holders is more credible in developing countries, where sovereign default risk is higher. Compared to developed economies, domestic credit in developing countries is also more sensitive to international capital inflows and should constrain policy‐makers’ ability to impact lending dynamics (Balding, 2011; Campello, 2013; Kaplan, 2013). Accordingly, we expect to see the mediating effects of financial openness to be stronger in developing compared to developed economies.…”
Section: Synthesis and Hypothesesmentioning
confidence: 99%
“…They found that while an increase in public debt increased the CDS premium, the most effective variable on CDS was unemployment and the least effective variable was inflation. Balding (2011) examined the relationship between CDS pricing and elections in 13 emerging market economies for the period 2004-2007 and found that elections had statistically significant effect On CDS pricing. Longstaff, Pan, Pedersen & Singleton (2011) investigated the nature of CDS by examining the relationship between CDS spreads of 26 countries and country-specific factors of those countries and the relationship between CDS spreads and global financial variables.…”
Section: Introductionmentioning
confidence: 99%